2008
DOI: 10.1016/j.gca.2008.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopic evidence in support of active microbial methane cycling in low-temperature diffuse flow vents at 9°50′N East Pacific Rise

Abstract: 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 99 publications
3
51
0
Order By: Relevance
“…6. The estimated H 2 /CH 4 ratio of the HAKUREI fluid (0.022) is significantly lower than those of sediment-starved hydrothermal sites (>1, Welhan and Craig, 1983;Charlou et al, 2002;Kumagai et al, 2008;Proskurowski et al, 2008;Takai et al, 2008) that correspond to abiotic gas. Notably, the H 2 /CH 4 ratio of the HAKUREI fluid was comparable with those of thermogenic gases produced by hydrothermal experiment using the Guaymas Basin sediment (0.02~0.2: Seewald et al, 1994) as well as other sediment-related hydrothermal sites (Fig.…”
Section: H 2 /Ch 4 Ratiomentioning
confidence: 74%
See 1 more Smart Citation
“…6. The estimated H 2 /CH 4 ratio of the HAKUREI fluid (0.022) is significantly lower than those of sediment-starved hydrothermal sites (>1, Welhan and Craig, 1983;Charlou et al, 2002;Kumagai et al, 2008;Proskurowski et al, 2008;Takai et al, 2008) that correspond to abiotic gas. Notably, the H 2 /CH 4 ratio of the HAKUREI fluid was comparable with those of thermogenic gases produced by hydrothermal experiment using the Guaymas Basin sediment (0.02~0.2: Seewald et al, 1994) as well as other sediment-related hydrothermal sites (Fig.…”
Section: H 2 /Ch 4 Ratiomentioning
confidence: 74%
“…Although microbial contribution accounts for the δ 13 C value in the HAKUREI plume as well as that in the JADE plume, the enriched δ 13 C value in the estimated endmember HAKUREI fluid can be also derived from involvement of isotopically heavy methane from the fluid-sediment interaction (~-23‰: Seewald et al, 1994) into upwelling fluid, which has δ 13 C value as low as that observed in the JADE fluid (-36~-41‰). Alternatively, temporal change of the endmember δ 13 C value in the JADE fluid for last decades is also possible (e.g., Proskurowski et al, 2008). If the δ 13 C value in the JADE fluid at 2008 is similar to those estimated from our plume observation, involvement of plume alteration and fluid-sediment interaction is not required to explain the plume data.…”
Section: Carbon Isotope Ratio In Endmember Fluidmentioning
confidence: 78%
“…Two segments north of Kairei and 1000 m deeper on the same ridge, the Edmond vent field exhibits some of the lowest hydrogen concentrations that have been reported, 0.02-0.2 mmol kg −1 . A large range of hydrogen concentrations has also been observed on the EPR at 9°50′N, where eruptive events occurred in 1991and 1992[Von Damm and Lilley, 2004Proskurowski et al, 2008a]. The high concentrations occur in the high-temperature vent fluids, and these concentrations decrease in time following the eruptive events.…”
Section: Hydrogen Flux From Mid-ocean Ridgesmentioning
confidence: 95%
“…This method provided the sensitivity to measure the low gas concentrations of background seawater (CH 4 : 0.5-1nM, H 2 : 0.1-0.5 nM). Hydrothermal fluids are enriched in both CH 4 and H 2 (Lilley et al, 1982;Proskurowski et al, 2008).…”
Section: Vent Plume Gsosmentioning
confidence: 99%